Identifying Optimal Locations for Potential Temporary Community Clinics During Public Health Emergencies. (January 2023) - Mohagheghi, Salman; Gharipour, Mohammad; DeClercq, Caitlin; Bui, Andrew; Tyne, Intisar Ameen
Objectives: This article argues that community healthcare clinics managed by dedicated medical professionals who are familiar with the special needs of the local community may serve as effective alternatives to centralized hospitals and medical facilities, which may be disconnected from these local communities. Background: The literature indicates that socioeconomic factors that affect an individual's ability to seek medical help when needed can cause vulnerability to public health emergencies. These factors include belonging to lower income populations, being African American, being dependent due to age (below 18 or above 65) or disability, being an immigrant, English-language ability, access to transportation means, and the strength of an individual's social network. Method: This study aims at developing a multifaceted methodology to identify optimal locations for deployment of temporary healthcare clinics to address health disparity issues among socially vulnerable populations, especially during pandemics and public health crises. This case study looks at the Health Enterprise Zone (HEZ) in Baltimore and ranks Census tracts based on their vulnerability, using two novel health vulnerability indices and considering their locations. Results: Using the proposed methodology, the optimal tracts within the HEZ are identified as potential locations for deploying temporary healthcare clinics. Conclusion: The analysis of vulnerabilities to public health emergencies based on socioeconomic factors can assist in identifying potential locations for setting up temporary healthcare clinics with the goal of assisting socially vulnerable populations during outbreaks and pandemics.